PRODUCTIVITY AND ITS DETERMINANTS IN ISLAMIC BANKS: EVIDENCE FROM INDONESIA - Siti Annita Otaviya; Lina Nugraha Rani (Bank Indonesia, 2020)
This study aims to determine the level of productivity of Islamic banks in Indonesia during the period 2011-2018 using indicators of Total Factor Productivity Change (TFPCH) or changes in productivity, and to identify potential determinants of TFPCH. In the first stage, the Malmquist Productivity Index (MPI) is employed to analyse the TFPCH of eight Islamic banks operating between 2011 and 2018. In the second stage, panel data regression is applied to assess the potential determinants of TFPCH. The research findings show that Indonesian Islamic banks experience productivity growth, and that the Technical/Technological Change (TECHCH) component has had a significant influence on this growth, with the GDP and BI rate variables being potential determinants of TFPCH. The research contributes to the renewal of interest in studies of Islamic bank productivity performance in Indonesia, and is accompanied by analysis of the specific determinants of the potential of private banks and the macroeconomics of productivity, research on which is still limited in the related literature.